‘Alimentary Assemblages’ at Intersections: Food, (Queer) Bodies, and Intersectionality in Marusya Bociurkiw’s Comfort Food for Breakups: The Memoir of a Hungry Girl (2007) - Suchacka, Weronika (Studia Anglica Posnaniensia, 2020)
Clearly devoted to the analysis of various issues of belonging, the work of Marusya Bociurkiw, a Ukrainian-Canadian queer writer, director, academic, and activist, examines culture, memory, history, and subjectivity in a fascinatingly unique way. Such a thematic composition is, however, not the only aspect that visibly marks and unities Bociurkiw’s multi-generic oeuvre; what clearly stands out as yet another distinguishing characteristic that Bociurkiw’s works have in common is the idea that seems to stand behind their creation – an impelling notion that “[t]o have one’s belonging lodged in a metaphor is voluptuous intrigue” (Brand 2001: 18). Consequently, what Bociurkiw’s works vividly portray is the writing-self “in search of its most resonant metaphor” (Brand 2001: 19). In one of her works, Comfort Food for Breakups: The Memoir of a Hungry Girl (2007), this metaphor is food as the art of food-making and the act of eating become here a crucial background against which the issues of belonging are played out. The aim of this article is thus to show how Bociurkiw finds her way of discussing various aspects of subjectivity by means of writing about food, whether about preparing it, tasting it, or recollecting its preparation and tastes. Ultimately, however, the article is to prove that food in Bociurkiw’s memoir not only reflects identity but is presented as a vital site of intersectionality. Thus, embedded in intersectionality discourse, and particularly instructed by Vivian May’s Pursuing Intersectionality, Unsettling Dominant Imaginaries (2015), the analysis of Comfort Food for Breakups is carried out from an interdisciplinary perspective because it is simultaneously grounded in food studies theory, i.e., the ideas developed by Elspeth Probyn in Carnal Appetites: FoodSexIdentities (2000), confirming, in this way, that vital connections can and should be made between the two, ostensibly unrelated, fields of study.